The relationship of tenure to job satisfaction and satisfactoriness among Cebu Redemptorist Lay Cooperators - Awayan, Portia Sylvia D. (Animo Repository, 1999)
This study investigates the levels of job satisfaction and satisfactoriness among the Cebu Redemptorist Lay Cooperators (CRLCs) in the Visayas and Mindanao, and determines the relationship between these and tenure. The study also finds out whether the levels of job satisfaction and satisfactoriness are affected by the type of work, age, gender, civil status, and educational attainment of the respondents. This study uses the descriptive-correlational methods of research. The Minnesota Satisfaction Questionnaire (MSQ) and the Minnesota Satisfactoriness Scores (MSS) were administered to 60 lay cooperators of the Redemptorists. Using an interview schedule, both highest and lowest scores were obtained. The results indicated that as a group, the respondents had a low level of general job satisfaction (15 percentile), while at the same time they were regarded as satisfactory as a group (57 percentile) by the Redemptorist organization. No significant relationship was found between tenure and the general job satisfaction and general job satisfactoriness scores among the CRLCs. No significant differences were found in job satisfaction of CRLCs grouped according to age, gender, and educational attainment, but significant differences in satisfaction were noted according to civil status and type of work. Regarding job satisfactoriness of the respondents, no significant differences were indicated based on the demographic variables. The study concluded that the Theory of Work Adjustment was not operational in this kind of setting. The study did not confirm the hypothesis that tenure is related to job satisfaction and job satisfactoriness. The CRLCs were not satisfied with their job, but they were regarded as satisfactory workers by the Redemptorist organization. There were no significant differences in job satisfaction and satisfactoriness scores of CRLCs differing in age, gender, and educational attainment but significant differences were noted in satisfaction according to type of work and civil status.